SUAS-based NDVI and RGB image for remote landscape and environmental monitoring on university campus - Yusof, Ahmad Anas; Yahya, Mohd Faid; Mohamed Nor, Mohd Khairi; Miskon, Muhammad Fahmi (2023)
This project measures NIR and visible spectrum reflectance on the land- scape of the Universiti Teknikal Malaysia Melaka Main Campus in Durian Tunggal,